TEOLOGI PENDIDIKAN DALAM WACANA KEILMUAN KONTEMPORER - Markarma, Andi (State Institute of Islamic Studies (IAIN) Palu, 2013)
Abstract. This paper rests on the assumption that education is a scientific activity. In the perspective of philosophy of science, the most central issue is the issue of the nature of science and the growth of science. Contemporary scholarly discourse questioned how the consequences of building science to education. This paper confirms that the concept and the actual praxis of education are associated with scientific problems. However, the end of the affirmation is to show that there are other problems also began to be touched by contemporary scientific discourse, the problem of faith, the principle of life, and faith in relation to education. Problem is called the